Changes in the Antioxidant Potential of Nori Sheets During in vitro Digestion with Pepsin. Issue 2 (7th February 2017) - Parimelazhagan, Indumathi; Mehta, Alka
ABSTRACT: Nori, the dried sheets of Porphyra, is a popular edible seaweed and a potential source of high quality protein, vitamins, and minerals. In the present study, the antioxidant potential of Nori has been investigated. For this purpose, an aqueous extract was obtained by soaking powdered Nori in KCl-HCl buffer and hydrolyzing it with pepsin. The antioxidant activity of aqueous extract of crude as well as pepsin hydrolyzate was evaluated using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, reducing power, total antioxidant capacity and lipid peroxidation by thiobarbituric acid reactive substances (TBARS) and compared with L-ascorbic acid. After hydrolysis, the scavenging ability and inhibition of lipid per oxide was doubled, and a sevenfold increase in reducing power activity was observed. The small molecular weight fractions (F-II) of hydrolyzate obtained after gel filtration showed further increase in the activity. These results demonstrate that hydrolysis produces better antioxidants that could be used as an alternative to synthetic antioxidants.